A risky undertaking for Loretta Singletary : a Samuel Craddock mystery - Shames, Terry (Shames, Terry. Samuel Craddock mystery., 2019)
"After using an online dating site for senior citizens, town favorite Loretta Singletary goes missing. Chief Samuel Craddock's old friend Loretta Singletary has undergone a transformation, with a new hairstyle and modern clothes. He thinks nothing of it until she disappears. Only then does he find out that she has been flirting in an online dating site for small-town participants. When a woman from a nearby town who frequented the same site is murdered, Craddock becomes alarmed. Evidence shows that Loretta was lured to a meeting with a Mr. Hart, who also corresponded with the murdered woman. Will Craddock be able to find Loretta before she suffers the same fate?"--